2022
DOI: 10.3390/molecules27113624
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Synthetic Potential of γ-Lactam Derivatives Obtained from a Multicomponent Reaction—Applications as Antiproliferative Agents

Abstract: A study on the reactivity of 3-amino α,β-unsaturated γ-lactam derivatives obtained from a multicomponent reaction is presented. Key features of the substrates are the presence of an endocyclic α,β-unsaturated amide moiety and an enamine functionality. Following different synthetic protocols, the functionalization at three different positions of the lactam core is achieved. In the presence of a soft base, under thermodynamic conditions, the functionalization at C-4 takes place where the substrates behave as ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…According to the number of atoms in the ring, they are classified as α-lactams, β-lactams, γ-lactams, and δ-lactams [15]. γ-lactams substituted in different positions have been used as building blocks for the synthesis of diverse bioactive compounds, and they have been investigated for their potential therapeutic applications in various diseases, including cancer, infectious diseases, and diabetes [16][17][18]. Therefore, several compounds, natural and non-natural, with a γ-lactam core in their structure have been shown to have a broad range of biological activities, including antimicrobial, antiproliferative, and anti-inflammatory activities, highlighting the potential of γ-lactams in the development of new drugs [19].…”
Section: In Silico Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the number of atoms in the ring, they are classified as α-lactams, β-lactams, γ-lactams, and δ-lactams [15]. γ-lactams substituted in different positions have been used as building blocks for the synthesis of diverse bioactive compounds, and they have been investigated for their potential therapeutic applications in various diseases, including cancer, infectious diseases, and diabetes [16][17][18]. Therefore, several compounds, natural and non-natural, with a γ-lactam core in their structure have been shown to have a broad range of biological activities, including antimicrobial, antiproliferative, and anti-inflammatory activities, highlighting the potential of γ-lactams in the development of new drugs [19].…”
Section: In Silico Resultsmentioning
confidence: 99%
“…Regarding anti-inflammatory activity, some studies have revealed that the γ-lactam core could be involved in the inhibition of tumor necrosis factor-α (TNF-α), cyclooxygenase-2 (COX-2), and nuclear factor kappa B (NF-B), which are involved in the inflammatory response [16][17][18]. Furthermore, some compounds having a γ-lactam have been shown to inhibit the formation of advanced glycation end products (AGEs) [20].…”
Section: In Silico Resultsmentioning
confidence: 99%
“…In this regard, very recently, we have reported an enantioselective aza-Reformatsky reaction of α-phosphorylated ketimines that leads to the formation of tetrasubstituted α-aminophosphonate derivatives [51]. In view of the interesting properties of aspartic acid derivatives and the potential of the isosteric substitution of a carboxylate by a phosphonate group, the corresponding phosphorus analogs of aspartic acid may be very interesting substrates from a biological point of view According to this, as part of our ongoing research into the identification of new chemotherapeutic agents [52][53][54], with a special focus on organophosphorus derivatives [55][56][57], we thought that the preparation of a wide family of phosphorated analogs of aspartic acid and the study of their anticancer properties would be an interesting contribution to the field of organic and medicinal chemistry. For all the reasons mentioned above, herein, we report a general method for the synthesis of tetrasubstituted phosphorated analogs of aspartic acid through an aza-Reformatsky reaction of αketiminophosphonates and the evaluation of their in vitro cytotoxic activity against several cancer cell lines.…”
Section: Chemistrymentioning
confidence: 99%